Influence of hydrogen bubbles adhering to the exposed surface on the corrosion rate of magnesium alloys AZ31 and AZ61 in sodium chloride solution. Issue 6 (7th November 2016) - Feliu, S.; García‐Galvan, F. R.; Llorente, I.; Diaz, L.; Simancas, J.
Abstract : The influence of the presence of hydrogen bubbles adhered to the corroding specimen surface on the EIS estimations of corrosion rate of magnesium alloys is considered. The EIS corrosion rates for AZ31 specimens exposing a small area were four times higher than the real values determined by gravimetric or hydrogen evolution measurements. In contrast, no significant differences in the corrosion rate have been observed in the case of the AZ61 specimens. A progressive deterioration in the protective properties of the corrosion products layer formed during the test was observed only on AZ31 specimens exposing a small area. Abstract : Occasional occurrence of abnormally elevated corrosion rates in testing AZ31 alloy. Connection between anomalous results and some characteristics of the exposed surface. Possible effect of hydrogen bubbles adhered to the corroding surface of AZ31 alloy.